New Therapeutic Tools to Shape Monocyte Functional Phenotypes in Leishmaniasis - Vellozo, Natália S.; Rigoni, Thaís S.; Lopes, Marcela F. (Frontiers in Immunology, 2021)
In the innate immunity to Leishmania infection tissue-resident macrophages and inflammatory monocytes accumulate host-cell, effector, and efferocytosis functions. In addition, neutrophils, as host, effector, and apoptotic cells, as well as tissue-resident and monocyte-derived dendritic cells (DCs) imprint innate and adaptive immunity to Leishmania parasites. Macrophages develop phenotypes ranging from antimicrobial M1 to parasite-permissive M2, depending on mouse strain, Leishmania species, and T-cell cytokines. The Th1 (IFN-γ) and Th2 (IL-4) cytokines, which induce classically-activated (M1) or alternatively-activated (M2) macrophages, underlie resistance versus susceptibility to leishmaniasis. While macrophage phenotypes have been well discussed, new developments addressed the monocyte functional phenotypes in Leishmania infection. Here, we will emphasize the role of inflammatory monocytes to access how potential host-directed therapies for leishmaniasis, such as all-trans-retinoic acid (ATRA) and the ligand of Receptor Activator of Nuclear Factor-Kappa B (RANKL) might modulate immunity to Leishmania infection, by directly targeting monocytes to develop M1 or M2 phenotypes.